2007
DOI: 10.1097/01.ccm.0000251639.05135.e0
|View full text |Cite
|
Sign up to set email alerts
|

Advanced age exacerbates the pulmonary inflammatory response after lipopolysaccharide exposure

Abstract: The hyperreactive systemic inflammatory response seen in aged individuals after lipopolysaccharide administration is accompanied by an exacerbated pulmonary inflammatory response, which may contribute to the higher mortality seen in the aged given an inflammatory insult.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
59
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 97 publications
(62 citation statements)
references
References 52 publications
2
59
1
Order By: Relevance
“…Accordingly, we also found approximately twice the number of neutrophils in the lungs of aged mice following challenge at this time point. A similar finding was reported by Gomez et al who, after intraperitoneal injection of lipopolysaccharide (LPS) in mice, observed significantly increased alveolar cell counts in aged mice compared to young counterparts 36 . While poor chemotaxis of neutrophils from old donors has been reported 37 , those studies were performed using human neutrophils isolated from whole blood.…”
Section: Discussionsupporting
confidence: 87%
“…Accordingly, we also found approximately twice the number of neutrophils in the lungs of aged mice following challenge at this time point. A similar finding was reported by Gomez et al who, after intraperitoneal injection of lipopolysaccharide (LPS) in mice, observed significantly increased alveolar cell counts in aged mice compared to young counterparts 36 . While poor chemotaxis of neutrophils from old donors has been reported 37 , those studies were performed using human neutrophils isolated from whole blood.…”
Section: Discussionsupporting
confidence: 87%
“…Gomez et al . [21] inoculated lipopolysaccharide (from P. aeruginosa ) into the lungs of BALB/c mice and observed that the transcription levels of MIP-2 and KC in elderly mice were markedly higher than in young mice. In addition, PMN infiltration was greater in the elderly group.…”
Section: Discussionmentioning
confidence: 99%
“…In humans and animals, acute lung injury is generally more serious and is associated with higher mortality at advanced ages (Antonini et al 2001;Ely et al 2002;Gomez et al 2007). We have previously reported prolonged and enhanced neutrophilic inflammation in the lungs of aged mice, as compared with young mice, after LPS intratracheal administration, in which age-related decreases in lung VEGF expression and prolonged overexpression of neutrophilic chemokines were observed (Ito et al 2005(Ito et al , 2007.…”
Section: Introductionmentioning
confidence: 93%